In search of wisdom : life-changing truths in the Book of Proverbs - Meyer, Joyce, 1943- (FaithWords, 2021)
"The book of Proverbs is a treasure trove of spiritual and practical wisdom that equips us to live our best lives. Knowledge is important, but if it isn't converted into action, it fails to create transformational change in our lives. It is important to gain a thoughtful and practical understanding of the seven foundational principles in the book of Proverbs: Wisdom, Understanding, Prudence, Knowledge, Discretion, Discernment, and Fear of the Lord. If we desire to possess these qualities, we must make a commitment to a deeper understanding and implementation of these values in our daily lives. Featuring inspiring questions and space for thoughtful reflection, In Search of Wisdom will enlighten you with God's understanding and teach you the foundational principles and secure God's help in practicing them"--